Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a.
\(\frac{4}{7}x-\frac{2}{3}=\frac{1}{5}\)
\(\frac{4}{7}x=\frac{1}{5}+\frac{2}{3}\)
\(\frac{4}{7}x=\frac{3+10}{15}\)
\(\frac{4}{7}x=\frac{13}{15}\)
\(x=\frac{13}{15}\div\frac{4}{7}\)
\(x=\frac{13}{15}\times\frac{7}{4}\)
\(x=\frac{91}{60}\)
b.
\(\frac{2}{9}+\frac{7}{8}x=\frac{1}{3}\)
\(\frac{7}{8}x=\frac{1}{3}-\frac{2}{9}\)
\(\frac{7}{8}x=\frac{3-2}{9}\)
\(\frac{7}{8}x=\frac{1}{9}\)
\(x=\frac{1}{9}\div\frac{7}{8}\)
\(x=\frac{1}{9}\times\frac{8}{7}\)
\(x=\frac{8}{63}\)
Chúc bạn học tốt
c) pt <=> \(x-\frac{21}{5}=\frac{23}{7}< =>x=\frac{23}{7}+\frac{21}{5}=\frac{262}{35}\)
vậy x = \(\frac{262}{35}\)
d) \(x-\frac{3}{4}=\frac{51}{8}< =>x=\frac{51}{8}+\frac{3}{4}=\frac{57}{8}\)
vậy x = \(\frac{57}{8}\)
e) pt <=> \(\frac{7}{8}:x=\frac{7}{2}< =>\frac{7}{8}.\frac{1}{x}=\frac{7}{2}< =>\frac{7}{8x}=\frac{7}{2}< =>56x=14< =>x=\frac{14}{56}=\frac{1}{4}\)
vậy x = \(\frac{1}{4}\)
a) pt <=> \(x+\frac{11}{4}=\frac{17}{3}< =>x=\frac{17}{3}-\frac{11}{4}=\frac{35}{12}\)
vậy x = \(\frac{35}{12}\)
b) pt <=> \(\frac{x.7}{2}=\frac{19}{4}< =>x=\frac{19.2}{4.7}=\frac{38}{28}=\frac{19}{14}\)
vậy x = \(\frac{19}{14}\)
b) \(\frac{2}{9}+\frac{7}{8}.x=\frac{1}{3}\)
\(\frac{1}{3}-\frac{2}{9}=\frac{7}{8}.x\)
\(\frac{7}{8}.x=\frac{1}{9}\)
\(x=\frac{1}{9}:\frac{7}{8}\)
\(x=\frac{8}{63}\)
c) \(\frac{4}{5}+\frac{5}{7}:x=\frac{1}{3}\)
\(\frac{5}{7}:x=\frac{1}{3}-\frac{4}{5}\)
\(\frac{5}{7}:x=\frac{-7}{15}\)
\(x=\frac{5}{7}:\frac{-7}{15}\)
\(x=\frac{75}{-49}\)
b) \(\frac{2}{9}+\frac{7}{8}x=\frac{1}{3}\)
\(\frac{7}{8}x=\frac{1}{3}-\frac{2}{9}=\frac{1}{9}\)
\(x=\frac{1}{9}:\frac{7}{8}=\frac{8}{63}\)
c) \(\frac{4}{5}+\frac{5}{7}:x=\frac{1}{3}\)
\(\frac{5}{7}:x=\frac{1}{3}-\frac{4}{5}=-\frac{7}{15}\)
\(x=\frac{5}{7}:\left(-\frac{7}{15}\right)=-\frac{75}{49}\)
\(\frac{10}{3}.x+\frac{67}{4}=\frac{53}{4}\)
\(\frac{10}{3}.x=\frac{53}{4}-\frac{67}{4}\)
\(\frac{10}{3}.x=-\frac{7}{2}\)
\(x=-\frac{7}{2}:\frac{10}{3}\)
\(x=-\frac{21}{20}\)
1. \(x=\frac{61}{42}\)
2. \(x=\frac{-36}{5}\)
3. \(x=\frac{13}{11}\)
4. \(x=\frac{1}{12}\)
5.\(x=\frac{-5}{2}\)
a) X-4,2=58,4-24,9
X-4,2= 33,5
X= 33,5+4,2
X=37,7
b) \(\frac{4}{5}-X=\frac{1}{5}+\frac{2}{7}\)
\(\frac{4}{5}-X=\frac{17}{35}\)
\(X=\frac{4}{5}-\frac{17}{35}\)
\(X=\frac{5}{7}\)
c)\(X-140:35=270\)
\(X-4=270\)
X=274
d) 3.X + 2.X = 25
X.(3+2) = 25
X = 25:(3+2)
X=5
a) b) \(\frac{4}{5}-x=\frac{1}{5}+\frac{2}{7}\)
x – 4,2 = 58,4 – 24,9 \(\frac{4}{5}-x=\frac{17}{35}\)
x – 4,2 = 33,5 \(x=\frac{4}{5}-\frac{17}{35}\)
x = 33,5 + 4,2 \(x=\frac{11}{35}\)
x = 37,7
c) d) \(3\times x+2\times x=25\)
x – 140 : 35 = 270 \(x\times\left(3+2\right)=25\)
x - 4 = 270 \(x\times5=25\)
x = 270 + 4 \(x=25\div5\)
x = 274 \(x=5\)
\(3\times x-x\times2=7\frac{3}{8}+\frac{5}{8}\)
\(x\left(3-2\right)=8\)
\(x=8\)
3 nhân x - x nhân 2 = 7 3/8 + 5/8
x nhân (3-2) = 7 3/8 + 5/8
x = 7 3/8 + 5/8